2017
DOI: 10.1038/nrmicro.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

Targeting microbial biofilms: current and prospective therapeutic strategies

Abstract: Biofilm formation is a key virulence factor for a wide range of microorganisms that cause chronic infections. The multifactorial nature of biofilm development and drug tolerance imposes great challenges for the use of conventional antimicrobials, and indicates the need for multi-targeted or combinatorial therapies. In this review, we focus on current therapeutic strategies and those that are under development that target vital structural and functional traits of microbial biofilms and drug tolerance mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
1,139
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,362 publications
(1,219 citation statements)
references
References 160 publications
6
1,139
0
12
Order By: Relevance
“…In bacterial biofilm communities, such as subgingival biofilms, bacteria are surrounded by protective extracellular matrices (EMs), which are currently under intensive investigation, and novel ways of treating biofilm infections are being developed (for a review, see ref. [8]). EMs consist of proteins, extracellular DNA (eDNA) and polysaccharides, such as poly-N-acetylglucosamine (PGA), which is the major polysaccharide in A. actinomycetemcomitans biofilms [9].…”
Section: Introductionmentioning
confidence: 99%
“…In bacterial biofilm communities, such as subgingival biofilms, bacteria are surrounded by protective extracellular matrices (EMs), which are currently under intensive investigation, and novel ways of treating biofilm infections are being developed (for a review, see ref. [8]). EMs consist of proteins, extracellular DNA (eDNA) and polysaccharides, such as poly-N-acetylglucosamine (PGA), which is the major polysaccharide in A. actinomycetemcomitans biofilms [9].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, SurgihoneyRO reduced the viability of NTHi biofilms 4-log when treating with 71–142 g/L and 5-log when treating with 213 g/L, confirming that the bioengineering process enhanced the antibacterial efficacy, with 25.7 µM being the minimum effective concentration of H 2 O 2 . To overcome the recalcitrant nature of biofilms, it is becoming widely recognised that combination treatments targeting various aspects of the biofilm are required 2. SurgihoneyRO was therefore tested as an adjuvant therapy with the conventional antibiotic co-amoxiclav.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecules like peptides and mannosides that have targeted these different adhesins have shown efficacy in prevention and treatment of both bacterial and fungal biofilm infections. Studies reported mannosides targeting the bacterial adhesin FimH prevented catheter-associated urinary tract infection (UTI) in mice [80]. Pharmaceutically active surface coatings have long been investigated to both prevent adhesion to an implanted device and kill planktonic bacteria in the vicinity of the device, thereby reducing the formation of biofilm.…”
Section: Biofilm Targeting Approachesmentioning
confidence: 99%
“…At the most rudimentary level, mature biofilms can be disturbed by mechanical means using water sprays and jets along with debridement of surgical site infections [81]. Alternatively, biofilm formation can be targeted at various stages throughout their life cycle [80] (Figure 6). During the initial phase of biofilm formation, bacteria attaching to the surface can be prevented by targeting cell-surface-associated adhesins (appendages, proteins and EPS).…”
Section: Biofilm Targeting Approachesmentioning
confidence: 99%